Central peripheral cannulas. Less catheter complications in critically ill patients - Ulenberg, Grzegorz; Czapiewski, Łukasz; Ulenberg, Agata; Humańska, Marzena (Journal of Education, Health and Sport, 2018)
Permanent venous access in patients in intensive care plays a key role in the healing process. A routine branches to assume a central venous catheter to the patient is called a vascular access to the central venous line using a venous or long time. An alternative to this type of injection is the circumferential introduction of central venous (PICC - peripherally inserted central catheter) using long catheters placed e.g.. A vein shoulder or ulna, which is associated with the lack of such serious complications as pneumothorax or catheter of a large artery, but due to the length of the catheter risk of thromboembolic complications is higher in relation to the central access.